STUDENTS’ PERCEPTION OF AND ENGAGEMENT IN REACTIVE ONLINE EDUCATION PROVIDED DURING THE COVID-19 PANDEMIC - Kanik, Mehmet (International Online Journal of Education and Teaching, 2021)
One of the consequences of the COVID-19 pandemic was school closures, which was also the case in North Cyprus. As a response to school closures, universities switched to online education. This study aims to investigate students' perception of and engagement in this reactive online education provided during the pandemic. To investigate the issue, an online survey was used. Forty-six college students responded to the survey and the results indicate that students had an overall negative perception of their experience in online education. However, they demonstrated high engagement with online education and had higher academic achievement in the semester when education moved online than the previous semester. Results have implications for future online course offerings during moments of crisis in considering possible factors that contribute to positive attitude, motivation, engagement, and academic achievement.